Prevention of vaginal vault prolapse occurrences post vaginal and abdominal hysterectomy. An evidence based case report. - Suskhan Djusad (Universitas Airlangga, 2021)
Objectives: To determine efficacy of the procedures which were performed during hysterectomy in preventing any complication, in the form of vaginal vault prolapse.Materials and Methods: Articles were searched through the databases, such as PubMed, Scopus, EBSCO-host, and Cochrane Library; resulting in three full text articles which were relevant to be critically reviewed. Those articles then were critically reviewed based on validity, importance, and applicability based on critical review tools from University of Oxford Centre-for Evidence Based Medicine (CEBM) 2011.Results: Findings from the articles showed that prevention procedures during hysterectomy such as McCall culdoplasty, Shull suspension, laparoscopic USP and ULS were effective in preventing future vaginal vault prolapse in women who underwent hysterectomy. Among the four procedures; McCall culdoplasty and Shull suspension provide the highest efficacy as prevention procedures. Other than that, both methods were capable to increase quality of life and sexual function post hysterectomy.Conclusion: Vaginal vault prolapse prevention procedures such as McCall culdoplasty, Shull suspension, laparoscopic USP and ULS were effective in preventing a vaginal vault prolapse. However, additional literatures are needed to support the utilization of these methods in clinical setting.